Displaying thinking about the features of Ukrainian national character in the works of Taras Shevchenko (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the peculiarities of Ukrainian national character reflected in Shevchenko’s works:  “Dug grave”, “The Great Cellar“,“To Osnovianenko“, “Standing in the village Subotovo“,“Gajdamaki“,“For the dead and the living“, “Walk with pleasure and not without morals“.  Particular emphasis is placed on poet’s understanding of close connection of Ukrainian national character features and their historical destiny.
Keywords: national character; the history; the people; the national ideal